Boric compounds as food preservatives
1926-06 1926 1920s 8 pages Private and Confidential. June 1926 No. 36 TRADES UNION CONGRESS LABOUR PARTY JOINT RESEARCH AND INFORMATION DEPARTMENT SCIENCE ADVISORY COMMITTEE BORIC COMPOUNDS AS FOOD PRESERVATIVES PRESERVATION OF FOOD. (1) It is not possible to deliver to consumers the total production of certain foodstuffs in a perfectly fresh condition. Preservation has rendered certain foodstuffs less costly and more generally available. (2) The various methods of preservation may be classified as chemical or physical. (3) It is doubtful if any method of preservation is absolute, i.e. in all cases changes occur which may affect the dietetic value of the foodstuff. (4) In relation to those foodstuffs which readily decompose the problem is not (a) shall we allow or forbid preservation, but rather (b) what is the best method of preservation? CHEMICAL OR PHYSICAL METHODS? (1) Chemical Methods. It has been considered a sound argument for the last 25 years that any substance which prevents the decomposition of foodstuffs may be expected to retard the analogous fermentative process of digestion. This belief is founded more on general observation than on any conclusive series of researches. On the other hand, none of the preservatives has been conclusively proved to be harmless. A number of people, of whom perhaps Sir Frederick Treves is one of the most important, have pointed out that the increase in cancer 292/840/1/3